2017
DOI: 10.1155/2017/6249685
|View full text |Cite
|
Sign up to set email alerts
|

MBD2 Regulates Th17 Cell Differentiation and Experimental Severe Asthma by Affecting IRF4 Expression

Abstract: Th17 cells and IL-17 participate in airway neutrophil infiltration characteristics in the pathogenesis of severe asthma. Methyl-CpG binding domain protein 2 (MBD2) expression increased in CD4+ T cells in peripheral blood samples of asthma patients. However, little is known about that epigenetic regulation of MBD2 in both immunological pathogenesis of experimental severe asthma and CD4+ T cell differentiation. Here, we established a neutrophil-predominant severe asthma model, which was characterized by airway h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 33 publications
2
31
0
Order By: Relevance
“…These genes could be acting intrinsically within CD8 T cells to influence development of CD62L+ memory CD8 T cells. However, Mbd2 is known to impact function of antigen-presenting cells and differentiation of CD4 T cells (Cook et al, 2015;Jia et al, 2017), suggesting that genes of interest may act extrinsically by modulating function of other cell types that regulate priming of CD8 T cells and/or the cytokine milieu during the response. Therefore, examination of the impact of these genes of interest on development of CD62L+ Tcm cells will need to include careful analysis of CD8 T cells themselves as well as other cell types that may impact CD8 T cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…These genes could be acting intrinsically within CD8 T cells to influence development of CD62L+ memory CD8 T cells. However, Mbd2 is known to impact function of antigen-presenting cells and differentiation of CD4 T cells (Cook et al, 2015;Jia et al, 2017), suggesting that genes of interest may act extrinsically by modulating function of other cell types that regulate priming of CD8 T cells and/or the cytokine milieu during the response. Therefore, examination of the impact of these genes of interest on development of CD62L+ Tcm cells will need to include careful analysis of CD8 T cells themselves as well as other cell types that may impact CD8 T cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Methylation of CpG island results in gene activation or inhibition but usually promotes repression, since the islands are located in the transcription start site (TSS) of genes [ 23 ]. Recently, our study found that methyl CpG binding domain protein 2-mediated Th17 differentiation in severe asthma is associated with IRF4 and SOCS3 expression, providing novel insight into epigenetic regulation and target for treatment in severe asthma [ 24 , 25 ]. A specific term “epimutation” is used in literature to denote the heritable genetic changes caused by DNA modifications [ 26 ].…”
Section: Dna Methylationmentioning
confidence: 99%
“…17 In a model of severe asthma disease, MBD2 was shown to regulate the differentiation of Th17 cells by promoting the expression of relevant important genes to ultimately affect the inflammatory response. 18 Moreover, reduced MBD2 expression has recently been found to enhance airway inflammation in bronchial epithelium in COPD. 19 Our previous work explored the downstream target genes of miR-301a-5p, and found there was a targeted regulatory relationship between miR-301a-5p and stromal cell-derived factor-1 (SDF-1/CXCL12), which is a member of the chemokine protein family.…”
Section: Introductionmentioning
confidence: 99%
“… 17 In a model of severe asthma disease, MBD2 was shown to regulate the differentiation of Th17 cells by promoting the expression of relevant important genes to ultimately affect the inflammatory response. 18 Moreover, reduced MBD2 expression has recently been found to enhance airway inflammation in bronchial epithelium in COPD. 19 …”
Section: Introductionmentioning
confidence: 99%